The Effect of Exchange Rate on Economic Growth of Nigeria - Uchechi, Ukangwa Jane; Iheukwumere, Ikechi Victor (Central Asian Journal of Innovations on Tourism Management and Finance, 2022)
This research work explored the effect of Nigeria’s exchange rate on the economic growth of Nigeria. It is focused on establishing the extent to which Naira rate have influenced economic growth from using data spanning between 1987 and 2018; and the extent to which the Naira rate has influenced inflation in Nigeria within the same time frame. This study however employed Ordinary Least Squares technique of analysis to construct a regression model to test stated hypotheses. Findings revealed that the Naira rate has no significant impact on economic growth in Nigeria and that the Naira rate has a significant influence on inflation rate in Naira. The study, therefore, recommends that the export base of Nigeria should be strengthened to ensure a sustainable impact and that local manufacturing should be fully encouraged.